VERTICAL AXIS WIND TURBINE DESIGN FOR MOVEMENT PERMANENT MAGNETIC GENERATORS OF AXIAL TYPE - sembodo, budi prijo; Koedijati, Titik; Jumali, Abdul (Tibuana, 2019)
One of the alternative energy source that can be developed is the Wind Power Plant. The need for electrical energy that continues to increase, it takes not a little time to build a power plant. System planners must also be able to see the possibilities of the development of the power system in the years to come. Indonesia is a country that has abundant energy resources, one of which is a source of wind energy. Indonesia which is an archipelagic country and one of the countries located on the equator is a factor, that Indonesia has abundant wind energy potential. In this study the output that produced is a renewable energy product, which is a power plant product in the coastal area. In the previous study a low-speed permanent magnet generator has been produced which can be driven by wind turbines which will be continued through the design of vertical type wind turbines. The results of this study can then be developed, especially for electricity generation products in the coastal region. In the process of planning and manufacturing vertical type wind turbines, to produce enough power to meet household electricity needs should be based on several factors that support the effectiveness of the power produced by the turbine, namely: Turbine Dimensions (Length and Blade Width), Material Strength , Shaft, Bearing and Generator Shaft